Socio-economic Inequality or Demographic Conditions: A Micro-level Analysis of Terrorism in Jharkhand. Issue 1 (July 2018) - Ouassini, Nabil; Verma, Arvind
A popular perception is that left-wing extremism has its roots in the phenomenon of socio-economic inequality. Yet, empirical work analysing this perception and exploring the links between left-wing extremism and socio-economic deprivation is limited. This article examines the relationship between socio-economic-demographic indices and left-wing extremism in the state of Jharkhand in India. The analysis tests the strength of the relationship linking left-wing terrorist incidents that occurred between the years of 2005 and March of 2012 and various socio-economic-demographic factors. The results suggest that the districts that report high incidents of terrorist attacks are not only linked to socio-economic inequality but also associated with socio-demographic conditions concerning state access and the lack of penetration by security and government agencies. In the conclusion, policy implications and future research for the state of Jharkhand are suggested.